Neuroprotective effects of sinapic acid involve the iron regulatory role on the rotenone-induced Parkinson’s disease model - Avcı, Bahattin (2023)
In the last decades, ferroptosis and its relationship with Parkinson’s disease have gained significant attention. Compounds that affect ferroptosis and iron-dependent pathways in particular, have possible candidates for study in this context.Sinapic acid is an iron-chelator and high antioxidant bioactive phenolic acid. Its neuroprotective action, due to the antioxidant capacity, has been shown in several experimental models.However, the relationship between iron and antioxidant actions is still misunderstood and therefore, in the current study, we tried to investigate the effects of sinapic acid in rotenone-induced Parkinson’s disease with the aspect of ferroptosis and iron-dependent alterations.The Parkinson’s disease model was induced by a single dose intrastriatal and intrategmental rotenone (5µg/µl) injection.Sinapic acid (30mg/ kg) was orally administered during a 28-day period after the Parkinson’s disease model was validated.Our results demonstrated that sinapic acid treatment attenuated rotenone-induced increase of serum transferrin and iron levels.Furthermore, sinapic acid inhibited rotenone-induced heme oxygenase-1(HO-1) increase and decrease of glutathione peroxidase-4 (GPx-4) levels in brain tissue. Also, sinapic acid treatment decreased motor impairment, likely as a result of the ameliorative effects on the tyrosine hydroxylase immunoreactivity loss after the rotenone insult.Our study suggests that the iron regulatory role of sinapic acid possibly plays a role in the protective effect on rotenone-induced neuronal damage.